Impact of achieving primary care targets in Type 2 diabetes on health outcomes and healthcare costs - Keng, M; Tsiachristas, A; Leal, J; Gray, A; Mihaylova, B (Wiley, 2019)
Aims In England and Wales, the National Diabetes Audit (NDA) assesses the quality of Type 2 diabetes (T2D) management in primary care using treatment targets for HbA1c ≤ 58mmol/mol, total cholesterol < 5mmol/L, and blood pressure ≤ 140/80mmHg. We quantify the impact of variation across general practitioners’ (GP) practices in achieving these targets on patients’ health outcomes and healthcare costs. Methods Summary characteristics of T2D patients from the 2015-2016 NDA were used to generate representative populations of T2D patients. The UKPDS Outcomes Model 2 was used to estimate patients’ long-term health outcomes and healthcare costs. The effects of achieving treatment targets on these outcomes were evaluated using regression models. Results Achieving more of the HbA1c, cholesterol and blood pressure targets led to lower incidences of diabetes-related complications. About 0.5 (95%CI: 0.4-0.6) QALYs and 0.6 (95%CI: 0.4-0.7) LYs were gained by T2D patient over lifetime for each additional target met. The projected healthcare cost savings arising from fewer diabetes-related complications with achieving one, two or three targets compared to none were £859 (95%CI: £553-£1165), £940 (95%CI: £485-£1395), and £1037 (95%CI: £414-£1660) over patient’s lifetime. A typical GP practice in the lowest performing decile (average 371 T2D patients per practice, with 27% achieving all targets) is projected to gain 201 (95%CI: 123-279) QALYs and 231 (95%CI: 133-329) LYs, if all its T2D patients achieved all three targets. Conclusions Substantial gains in health outcomes and reductions in healthcare cost could be achieved with further improvements in attainment of HbA1c, cholesterol and blood pressure targets for T2D patients.